Guidance and Counseling Advocacy Service for Handling Sexual Violence at IAIN Pontianak - Fazny, Bella Yugi; Nurrahmi, Hesty; Saputra, Randi; Maulita, Nadia (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
The phenomenon of sexual violence in higher education necessitates the provision of advocacy, guidance, and counseling services. The development of a manual for these services can assist micro-groups (students, faculty members, and educational staff) in gaining a deeper understanding of sexual education, advocacy services, and mechanisms for addressing sexual violence within the higher education environment. Research and development methods have been carried out through to the implementation and evaluation stages of the manual. The research findings indicate that the sexual violence advocacy, counseling, and guidance manual has achieved 93% alignment with the research objectives and the needs of the micro-groups. Evaluation results from its use among students confirm an 80% increase in students' knowledge. Therefore, the manual developed from this research can be implemented and further developed across academic programs at the university level.